2012
DOI: 10.1007/s12560-012-9079-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Viruses in Coastal Seawater Using Mytilus Galloprovincialis as an Accumulation Matrix

Abstract: The purpose of this study was to demonstrate that shellfish can be used to detect enteric viruses in marine waters where they are present at very low concentrations. Aqua-cultured mussels were placed in the sea just off the mouth of a drainage channel affected by human and animal faecal contamination. Samples were taken from the channel, the sea and the mussels at intervals over two 4-week periods. The samples were tested to verify the presence of both rotaviruses and E. coli. Rotaviruses were detected by Real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…HBoV can be discharged in untreated wastewaters through virus shedding and, consequently, disperse throughout water environments, as shown recently in Italy (30,31) and elsewhere (26,28,32). Bivalve mollusks concentrate several human pathogens transmitted by the fecal-oral route, including a wide range of enteric viruses (35)(36)(37), whose presence in these aquatic organisms may be evaluated to assess the safety of the product for human consumption (38) or for biomonitoring purposes (39,40).…”
Section: Resultsmentioning
confidence: 99%
“…HBoV can be discharged in untreated wastewaters through virus shedding and, consequently, disperse throughout water environments, as shown recently in Italy (30,31) and elsewhere (26,28,32). Bivalve mollusks concentrate several human pathogens transmitted by the fecal-oral route, including a wide range of enteric viruses (35)(36)(37), whose presence in these aquatic organisms may be evaluated to assess the safety of the product for human consumption (38) or for biomonitoring purposes (39,40).…”
Section: Resultsmentioning
confidence: 99%
“…Viruses were concentrated from water samples by the tangential flow ultrafiltration technique using polypropylene membranes with a 10‐KDa molecular weight cut‐off and a pore size of 0.001–0.01 μm. These filters have been used in previous studies to concentrate viruses present in water, particularly enteroviruses and bacteriophages, with a sensitivity of 1 viral particle/ mL of water sample analysed . To eliminate particulate matter, the samples were prefiltered with 12‐μm polypropylene membranes.…”
Section: Methodsmentioning
confidence: 99%
“…1). Here, previous studies had revealed the widespread presence of bacterial indicators of fecal contamination and RV (Grassi et al 2010;De Donno et al 2012).…”
Section: Methodsmentioning
confidence: 71%
“…The results of the investigations carried out in a 5-week period showed that the waters of the site in which the study was performed are affected by a continuous, although low, contamination of fecal origin deducible from concentration of E. coli. As previously described (Grassi et al 2010;De Donno et al 2012), such contamination could be caused by Castellana-Trafili channel that could carry into the bay several microorganism of fecal origin including Rotavirus that however was never directly detected in seawater. The salinity values, appreciably lower than the control point, confirm the presence of significant input of fresh water in marine environment.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation